REVIEW OF ISLAMIC LAW OF THE STRATEGY FOR THE EMPOWERMENT OF WAKAF FUNDS IN THE AL-QUR'AN WAKAF BOARD (BWA) YOGYAKARTA - Maulana Umar Inamul Hasan; Nurulia Shalehatun Nisa; Arum Al Fakih (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
Waqf is one of the teachings of Islam that has socio-economic value for the welfare of society. Along with the times, waqf is not only in the form of goods, but can also be in the form of money and productive waqf. In fact, this understanding of the development of waqf is not widely known by the public, including in the Yogyakarta area. Waqf has a big role in providing the benefits of waqf property in Indonesia. Good institutional administration and strategies in the utilization of waqf funds are very important aspects to pay attention to, in order to achieve the goals of the waqf itself. Each waqf institution has its own strategy to realize its vision and mission, as well as BWA Yogyakarta which has an innovative strategy in order to realize its programs. What is the strategy for utilizing waqf funds at BWA Yogyakarta? What is the strategy for utilizing waqf funds at BWA Yogyakarta in a normative and juridical review? The type of research carried out by the authors is field research, the nature of this research is prescriptive research, the approach used by the authors is a normative empirical approach with maslahah mursalah theory, the data source consists of primary data and secondary data, data collection techniques in the research consists of methods of observation, interviews, and documentation, and the frame of mind that the compiler uses in data analysis is the inductive method. The result of this research is that BWA Yogyakarta has three strategies, namely Expansion Strategy (Traffic), Prospect Funding Strategy, and Customer and Partner Strategy. The application of the three strategies of BWA Yogyakarta normatively is in accordance with the concept of maslahah mursalah, and juridically, the three strategies follow most of the regulations stipulated by law, namely Article 4, Article 5, Article 11, Article 21, Article 22, Article 28, Article 42, Article 43 of Law Number 41 of 2004 concerning Waqf, Government Regulation Number 42 of 2006 concerning Implementation of Law Number 41 of 2004, Article 22 paragraph 1 and the Fatwa Commission of the Indonesian Ulema Council (MUI) on 11 May 2002. However, the three strategies did not fully implement Article 21 of Law Number 41 of 2004 concerning waqf and Government Regulation Number 42 of 2006 article 26.